Chemical Composition, Yield and Contents of Essential Oil of Lavandula hybrida Reverchon Grown under Different Nitrogen Fertilizer, Plant Density and Location - ARABACI, OLCAY; BAYRAM, EMINE; BAYDAR, HASAN; FERHAN SAVRAN, A.; OZAY, NAZAN; Karadogan, Tahsin (Asian Journal of Chemistry, 2010)
Effect of nitrogen fertilizer and plant density on the essential oil content, yield and oil composition of Lavandula hybrida Reverchon (lavandin) grown under different ecological conditions for initiating cultivation in Turkey were studied in this research during consecutive three years. Essential oil content and essential oil yield were affected by the experimental factors such as, location, fertilizer, plant density and their interaction. Essential oil content depending on fertilizer and plant density was between 4.900-5.617, 5.733-6.483 and 4.567-5.283% for experimental years, Aydin, Isparta and Canakkale locations, respectively. Under non-nitrogen fertilizer condition 80 × 20 cm plant density would be advisable for Aydin and Canakkale locations and under nitrogen fertilizer condition, 60 × 20 cm plant density would be appropriate for all locations. L × Y × F × Pd (Location × Year × Fertilizer × Plant density) interaction was found for essential oil yield. The major component of essential oil composition in Lavandula hybrida Reverchon was linalool, and this component was followed by linalyl acetate, camphor and 1,8 cineole.